2021
DOI: 10.1039/d1ra06985c
|View full text |Cite
|
Sign up to set email alerts
|

Copper-mediated construction of benzothieno[3,2-b]benzofurans by intramolecular dehydrogenative C–O coupling reaction

Abstract: The construction of benzothieno[3,2-b]benzofurans via novel dehydrogenative C–H/O–H coupling reaction has been developed with excellent yields. Furthermore, three-to-six fused ring thienofuran compounds could be constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…When ligands O-Phenanthrene and X-Phos were added, no significant change was observed in yield (Table 1, entries [16][17]. Moreover, when this transformation was performed in the absence of a catalyst or base no progression in reaction was found (Table 1, entries [18][19], which implies that both catalyst and base play an extensive role in supervisory of the reaction.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…When ligands O-Phenanthrene and X-Phos were added, no significant change was observed in yield (Table 1, entries [16][17]. Moreover, when this transformation was performed in the absence of a catalyst or base no progression in reaction was found (Table 1, entries [18][19], which implies that both catalyst and base play an extensive role in supervisory of the reaction.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, K. Mitsudo and S. Suga group (Scheme 2) independently reported the synthesis of furan‐fused thienoacenes using Cu‐catalyzed dehydrogenative CO arylation [17]. Moreover, in 2021, B. Li and co‐workers (Scheme 3) developed copper‐mediated construction of benzothieno [3,2‐ b ] benzofuran by intramolecular CO coupling [18]. Taking clues from the above strategies through copper metal catalysis, we are tempted to synthesize 6‐methyl benzofuro[3,2‐ c ] quinoline through intramolecular dehydrogenative CO coupling, employing copper as a catalyst (our work, Scheme 4).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Li and co-workers introduced another method for the construction of benzothieno[3,2-b]benzofurans by a copper mediated intramolecular dehydrogenative CÀ O coupling reaction (Scheme 16). [28] This approach constitutes an improved version of the work reported by the same authors on the intramolecular Ullmann coupling of 2-(3-bromobenzothiophen-2-yl)phenols. [18] The substrates for the present methodology, 2-(benzo-thiophen-2-yl)phenol derivatives 56 were synthesized by the Suzuki coupling of functionalized 2-bromobenzothiophenes and 2-hydroxyphenylboronic acids.…”
Section: Synthetic Routes Towards Benzothieno[32-b]benzofuran 1 Amentioning
confidence: 97%
“…The method was found to be general for the synthesis of a range of substituted benzothieno The authors conducted control experiments and found that the reaction proceeded by a radical pathway (Scheme 17). [28] Based on these observations, they have proposed a mechanism starting with the generation of the phenoxide anion 57 by the action of the base on (benzo-thiophen-2-yl)phenol 56. Next, a single electron transfer takes place between 57 and Cu(OAc) 2 yielding the phenoxy radical 58 which undergoes a intramolecular cyclization to afford the radical intermediate 59.…”
Section: Synthetic Routes Towards Benzothieno[32-b]benzofuran 1 Amentioning
confidence: 99%
“…Related O -centered radicals, such as phenoxy radicals, generated from phenols via base-assisted copper-mediated oxidation, have also been exploited to prepare polycyclic oxygen-containing compounds through intramolecular dehydrogenative C–O coupling . Moreover, a range of easily accessible N -hydroxylamines, such as N -hydroxyphthalimides, N -hydroxybenzotriazoles, and N -hydroxamic acids, have also been identified as competent precursors to O -centered radicals and can engage in an array of copper-mediated intermolecular O -centered radical addition/coupling reactions (Scheme d).…”
Section: Radical-addition-based C–o Bond Formationmentioning
confidence: 99%